The Trading Game from Geographical, Ethical, Philosophical, Economic, Educational Science, Political and Social-Science Education’s Point of View: An Interdisciplinary-explorative Analysis - Applis, Stefan; Benthaus, Benjamin; Bruns-Junker, Anka; Engel, Juliane; Fögele, Janis; Gessner, Susann; Henn, Frank Michael; Hofmann, Jan; Loerwald, Dirk; Mehren, Rainer; Meixner, Maria; Müller, Stefan; et al. (Journal of Geography Education, 2019)
This paper analyzes the strengths and weaknesses of the Trading Game (https://www.christianaid.org. uk/schools/trading-game) in relation to teaching/learning processes from a geographical, ethical, philosophical, economic, educational sciences, political and social-sciences education perspective. Among others, the game’s main strengths are considered to be its ability to enable a change of perspective, to trigger a strong need for reflection on the part of the players, or to offer opportunities for ethical decision-making processes. On the other hand, the under-complexity of the game’s conception, subject-specific errors in relation to world trade and the danger of promoting misconceptions are criticized as weaknesses of the game.